New drugs in the treatment of chronic hepatitis C - R. Jimenez Galan; Á. Albacete Ramirez; P. Monje Agudo; Y. Borrego Izquierdo; R. Morillo Verdugo (Farmacia Hospitalaria, 2014)
Objectives: To analyze the efficacy and safety of the new direct antiviralagents (DAA) that will become the new therapeutic arsenal for thetreatment of hepatitis C. Methods:We carried out a research in the electronic database with thefollowing criteria: phase II and III clinical trials (CT) published until February2014. The Mesh term used was “chronic hepatitis C” and “therapy”.Studies with boceprevir or telaprevir were excluded. For theanalysis of efficacy, we evaluated the rate of Sustained Viral Response(SVR), and for the safety, side effects and safety-related discontinuationswere analyzed. Results: We included 24 CT that include associations with ribavirine(RBV) with or without peginterferon (PegINF) and associations of severalDAA. The results associated of daclatasvir with PegINF and RBVhave not been very successful. On the contrary, sofosbuvir presentsactivity in all viral genotypes . Sofosbuvir may be administered in freePegINF regimens. Around 90% of naïve patients achieve sustainedvirological response (RVS) and 80% in previously treated. In relation tosecond wave of NS3/4A protease inhibitors, simeprevir has achievedRVS in 90% of naïve patients and close to 80% in previously treated.The main combination of DAA were sofosbuvir and daclatasvir andsofosbuvir and ledipasvir. Both have achieved SVR in 100% of patientswho previously had virological failure after receiving a protease inhibitorregimen with boceprevir or telaprevir. Conclusions: The new generation of AAD for the treatment of hepatitisC will lead to higher response rates in all subtypes of patients withlower complexity regimens and better tolerated.